(untitled) (International Journal of Engineering Management Science, 2024)
This review paper explores the seismic performance of high-rise buildings with floating columns and shear walls. The paper discusses the interaction between floating columns and shear walls, including synergies, challenges, and strategies for optimizing their interaction. Additionally, the paper examines various seismic performance assessment methods and performance-based design approaches for high-rise buildings. Factors affecting the seismic performance of buildings with floating columns and shear walls are also analyzed. The paper concludes with a comprehensive overview of the design principles and considerations essential for ensuring the seismic resilience of high-rise buildings in seismically active regions.